Simulation Model Evaluation of CO2 Capture by Aqueous MEA Scrubbing for Heat Requirement Analyses. (July 2017) - Moioli, Stefania; Nagy, Tibor; Langé, Stefano; Pellegrini, Laura A.; Mizsey, Peter
Abstract: Carbon dioxide is a powerful greenhouse gas, whose massive presence in the atmosphere causes gradual global warming. Absorption by means of chemical solvents is the most commonly used process for CO2 removal. It can be applied to gaseous streams in power plants, natural gas, and refinery gas. Amine scrubbing is widely considered the most mature technology for PCC (post-combustion CO2 capture), and 30% wt. MEA aqueous solution can be taken as the baseline solvent to be used as reference for studies focused on modelling and simulation. Thermodynamics, kinetics and mass transfer influence the chemical absorption process. The thermodynamic model exerts an influence also on the determination of the overall heat of absorption of the acid gas in the solvent, being the heat released at chemical equilibrium related to the extent of reactions. Its estimation is of paramount importance, since it is directly related to the energy requirement at the reboiler of the solvent regeneration column and determines the temperature profile along the absorber. The model used in this work has been previously validated by comparison with data of absorption performances with regard to mass transfer phenomenon. In this work, results obtained from simulations have been checked against experimental data, by focusing on the thermodynamic framework and its influence on the evaluation of the reboiler duty, for possible energy saving solutions in scale-up design.